Prenatal nursing care for women living in private prison in Brazil (Research, Society and Development, 2023)
Objectives: To evaluate nursing care and understand the weaknesses faced by women during pregnancy in private prison. Justification: The present study is based on the need for improvements in the health care of incarcerated women, following the rights of public health services policies and the principles of the Unified Health System (SUS), associated with the executive, legislative and judicial powers from Brazil. Methodology: This is an integrative review, carried out through the survey of articles, through the databases: BVS, SciELO, BDENF, LILACS and Medline. For the search, literature between the years 2017 to 2022, in Portuguese and English, was selected. Result: Nursing care faces barriers that negatively impact the provision of a humanized and comprehensive service. Accordingly, women who live in prison deal with conditions of poor hygiene, constant institutional violence, impairment of mental and physical health, inadequate nutrition, judgments, prejudice in cases of homosexuality, use of handcuffs, difficulty in moving outside the walls and do not have cells. specific to meet the needs during the gestational period. Conclusion: The performance of prenatal nursing in the prison environment is highlighted in the provision of services, even facing difficulties such as lack of material and human resources, becoming a public health issue in Brazil. Consequently, pregnant women living in private prison experience inadequate prenatal consultations that intensify their weaknesses and vulnerabilities during the pregnancy-puerperal period.